Economic report of the President transmitted to the Congress, February, 1983 : together with the annual report of the Council of Economic Advisers - United States President; Council of Economic Advisers (U.S.) (Washington: United States Government Printing Press, 1983)
This is the Economic Report of the President (Ronald Reagan) transmitted to congress on February 1983, together with the annual report of the Council of Economic Advisers.
rpm 13/06/2017
Loans
Keywords: United States -- Economic policy; Economic policy; Economic report; United States